Effect of Humic Acid on Nutrient Availability and Yield of Upland Rice Inoculated with Biofertilizers in the Coastal Area - Tika Indriani; Yudhy Harini Bertham; Hasanudin Hasanudin; Prasetyo Prasetyo; Bilman Wilman Simanihuruk (TERRA : Journal of Land Restoration, 2022)
This study aims to determine the effect of humic acid on nutrient availability and upland rice production in coastal land. The research was carried out in June - November 2020 in the Beringin Raya Village, Muara Bangkahulu District, Bengkulu City. This study used a completely randomized block design with 2 factors. The first factor was the local Bengkulu upland rice variety, namely the Red upland rice variety and the White upland rice variety, while the second factor was the type of fertilizer, namely control (basic fertilizer only), humic acid, and fertilizer recommended for upland rice from BPTP (200 kg Urea ha-1, 100 kg SP36 ha-1, 100 kg KCl ha-1). The results showed that the administration of humic acid in both the White and Red varieties resulted in the best KCl pH. And if you look at the yield per plot, the upland rice of the Red variety is better when given humic acid, which has an increase of 7.4% g/plot, while the White variety has better results when given the recommended inorganic fertilizer, which is an increase of 12% g/plot. The Red variety had a higher soil pH, but had a number of pithy grains per panicle, and a lower grain content percentage than the White variety. The application of humic acid resulted in better KCl, CEC, and N-total pH, but had plant height, number of pithy grains per panicle, and yields per plot that were almost the same as recommended inorganic fertilizers.